Redefining the role of urban studies Early Career Academics in the post-COVID-19 university. Issue 4 (4th July 2022) - ,; Ahmed, Nabeela; Baker, Alexander G.; Bhattacharya, Akash; Cawood, Sally; Cabrera Pacheco, Ana Julia; Daniel, Mallo Maren; Grandi, Matheus; Grimaldo-Rodríguez, Christian O.; Guma, Prince K.; Habermehl, Victoria; Higgins, Katie; et al.
Abstract : We are an international collective of Early Career Academics (ECAs) who met throughout 2020 to explore the implications of COVID-19 on precarious academics. With this intervention, our aims are to voice commonly shared experiences and concerns and to reflect on the extent to which the pandemic offers opportunities to redefine Higher Education and research institutions, in a context of ongoing precarity and funding cuts. Specifically, we explore avenues to build solidarity across institutions and geographies, to ensure that the conduct of urban research, and support offered to ECAs, allows for more inclusivity, diversity, security and equitability.